Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: • Assess the Performance of Secondary School Principals in Jeddah to Achieve Saudi Arabia’s Vision Targets Accordance with the Hellinger’s Measure From Teachers View points Ms. Rogaiae Faisal Fadhil* ,Ms. Abrar Housain ALthabiani ,Prof. Hayat Mohammad Saad Alharbi • Smart Supervision for School Empowerment and Educational Performance Improvement: A Study in Saudi Public Education Ms. Maryam Abdullah Al-Luhaidan ,Ms. Mashael Aseer Al-Otaibi • The Technical readiness for Applying Modern Syllabus of Science at the Secondary Stage in Taif Governorate Mr. Abdullah Jaza Fayhan Al-Nafie • Degree of Public School Practice Total Quality Standards Central Gaza Strip, and Relationship to Educational Strategic Planning Effectiveness from Teachers’ View Ms. Sabreen Salman Mezyed, Co-Prof. Suleiman Hussain Al Muzayn • The Role of Community-Based Educational Initiatives in Sustaining Education During the Israeli Aggression on Gaza: A Parental Perspective Dr. Nael Hassan Adwan ,Mr. Subhi Rabee Shuaib • Strategic Leadership as a Contemporary Trend in Educational Institutions: An Analytical Study of the Concept, Dimensions, and Challenges in the Kingdom of Saudi Arabia Ms. Sarah Ajlan Al-Shahri • Validation of the World Health Organization’s Abbreviated Quality of Life Scale on a Sample of Children with Cancer at Rambam Hospital in Haifa، Palestinian Territories Mr. Adnan Mahmoud Otallah